Symbolic Interaction Between Muslim and Hindu Communities in The Periri Gumi Tradition in Batulayar Village, Batulayar District, West Lombok Regency - Rista Tri Ariani (Tabéq Care Center and UIN Mataram, 2025)
Periri Gumi is a traditional ritual that has been passed down from generation to generation as a form of gratitude to God Almighty for the harvest and safety, as well as an effort to maintain harmony between humans, nature, and God. This tradition is an important symbol in the social life of the diverse Batulayar community, where Muslims and Hindus live side by side. The purpose of this study is to understand how the cultural symbols contained in the Periri Gumi tradition are understood and interpreted by two religious communities, and how interactions built through this tradition foster harmony and social cohesion. This study uses a qualitative case study approach. Data collection techniques included direct observation, in-depth interviews with community leaders, religious leaders, and ritual participants, and documentation. Data analysis uses the symbolic interaction theory developed by Herbert Blumer, which emphasises the importance of meaning, symbols, and interaction processes in shaping social behaviour. The study’s results show that the Periri Gumi tradition has become a social and cultural space that enables harmonious interaction among religious communities. Symbols such as offerings, traditional processions, traditional clothing, music, and interfaith prayers serve as a medium of communication between communities. Each symbol is interpreted based on each party’s social experiences and religious beliefs, while still respecting the other party. This tradition not only strengthens local cultural identity but also serves as a means of social integration, reflecting values of tolerance, cooperation, and equality. Thus, Periri Gumi functions as an effective social mechanism in building bridges of dialogue and togetherness among religious communities amid the plurality of Batulayar society.